Effectiveness of citizen inquiry approach in promoting environmental knowledge of young people - Micheal Obakhavbaye (Academia Environmental Sciences and Sustainability)
The unsustainable and unsafe disposal of single-use plastics poses a major environmental risk to society. Although there have been global calls to transition from a linear economy to a circular economy for plastics, the participation of young people across communities is critical to the achievement of this goal. To advocate for the circular economy in their community, young people must be empowered with adequate knowledge about single-use plastics and the circular plastic economy. Therefore, this study investigates the effectiveness of the citizen inquiry approach in enhancing young people’s knowledge of issues concerning single-use plastics within the context of the circular economy. It situates the conceptual underpinnings of citizen inquiry within the framework of collaborative citizen science, fused with inquiry-based learning, and makes a concerted effort for participants to be coresearchers in the design, implementation, and knowledge creation in six-week quasi-experimental research. The study utilizes a quantitative data collection strategy, providing a pretest before the study and a posttest after the study using the same instrument to assess the change in participants’ procedural and declarative knowledge. The data is analyzed using descriptive and t-test statistics to evaluate the difference in means between test scores before and after the intervention. The t-test results reveal a statistically significant difference in the procedural knowledge (t(4) = 4.355, p = 0.006), the declarative knowledge (t(18) = 10.762, p < 0.001), and the overall knowledge (t(23) = 11.688, p < 0.001) of the participants as measured by the pre-posttest. The results demonstrated a considerable improvement in the participants’ procedural, declarative, and overall knowledge. The findings indicate that the citizen inquiry technique can democratize learning and the research process, but it requires the design to be contextualized.